ANALISIS YURIDIS KEDUDUKAN PERJANJIAN HOMOGLASI DALAM MENGAKHIRI KEPAILITAN SESUAI DENGAN UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Rahmat Marianus Sidabutar; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The Verdict of the Endorsement of the Treaty of Peace or often referred to as Homoglasi must have legal certainty in ending bankruptcy. Homoggation provides an important opportunity for the debtor to re-manage his property. Assets and Passiva of a company are important considerations in deciding the ratification of a peace agreement or homoglation. This is useful for ensuring business continuity and for the fulfillment of the content of the homoglation agreement. Article 166 Paragraph 1 provides a strict stipulation that the homoglasi agreement has a strong position to end bankruptcy and in Article 288 stating that Homoglasi has the legal standing to end the Postponement of Debt Payment Obligations. The Treaty of Peace which has been approved by the Commercial Court (Homoglasi) must have a definite legal effect to end the bankruptcy that befell the debtor and become the base of rights for both parties. Judge must be more careful in deciding any bankruptcy case that has ended with homoglasi for the creation of legal certainty that becomes the legal umbrella for the debtor and creditorThe purpose of this thesis writing is: First, to know how the legal position of verdict of endorsement of peace (Homoglasi) in ending bankruptcy in accordance with Law Number 37 Year 2004 About Bankruptcy and Delay of Obligation of Debt Payment, Second, What is the effect of law of verdict of endorsement of peace agreement (Homoglasi ) to the Company's bankruptcy status in view of Law Number 37 Year 2004 Concerning Bankruptcy and Suspension of Payment Obligations.This type of research is normative legal research or can be called also research doctrinal law. From the research result of the problem there are two main points that concluded, Firstly, the position of verdict of endorsement of peace agreement (Homoglasi) which is not able to give guarantee of legal certainty to debtor pursuant to Law Number 37 Year 2004 About Bankruptcy and Delay of Debt Payment Obligation. Second, the legal consequences of the Decision of the Peace Agreement which can not have legal certainty resulting from the position of the Ratification of the Peace Treaty Agreement which has no legal certainty in ending the bankruptcy of the debtor.Keywords: Legal Status- Homoggation- Law Effects